Gold Nanoparticles: Surfactant‐Free Shape Control of Gold Nanoparticles Enabled by Unified Theoretical Framework of Nanocrystal Synthesis (Adv. Mater. 21/2017). Issue 21 (June 2017) - Wall, Matthew A.; Harmsen, Stefan; Pal, Soumik; Zhang, Lihua; Arianna, Gianluca; Lombardi, John R.; Drain, Charles Michael; Kircher, Moritz F.
Abstract : Different gold‐nanoparticle shapes can be produced by a new surfactant‐free synthetic strategy presented by Moritz F. Kircher and co‐workers in article number1605622 . Gold‐nanorod formation in this method is driven by re‐entrant groove defects on the end facets. Nanoparticles synthesized by this approach demonstrate excellent surface‐enhanced Raman scattering and catalytic performance.